2021
DOI: 10.1177/1420326x211027614
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the wall implanted with heat pipes on indoor thermal environment

Abstract: In order to improve the utilization of solar energy absorbed by the building wall, a passive building technology, that is the wall implanted with heat pipes, had been proposed. In the present study, two rooms with the same environmental conditions were built, and the one with a wall implanted with heat pipes installed was taken as a test room and the other as a control. The dynamic heat transfer characteristics of a wall implanted with heat pipes in transition season and its impact on indoor thermal environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Hence, a new type of Trombe wall was modified by using PCMs as a storage material. 86,87 The recent literature investigated PCM-Trombe walls 88,89 and confirmed the reduction in energy use and improvement in the interior temperature.…”
Section: Pcm-double-skin Facade (Pcm-dsf)mentioning
confidence: 73%
“…Hence, a new type of Trombe wall was modified by using PCMs as a storage material. 86,87 The recent literature investigated PCM-Trombe walls 88,89 and confirmed the reduction in energy use and improvement in the interior temperature.…”
Section: Pcm-double-skin Facade (Pcm-dsf)mentioning
confidence: 73%
“…A frequent task that occurs within the building thermal technology concerns the determination and elimination of heat losses. [1][2][3][4] Building envelopes with their facades represent one of the main factors influencing the effective thermal performance of buildings. The computations of the heat losses of buildings are standardized.…”
Section: Introductionmentioning
confidence: 99%
“…Ivanov et al [ 17 ] revealed a numerical study of the risk of condensation over the exterior wall of a typical residential room, and the resulting surface and dew point temperature distribution are derived over the simulated exterior wall. Zhigang et al [ 18 ] studied the dynamic heat transfer characteristics of the wall with heat pipes implanted in transition season and its influence on the indoor thermal environment. Xie et al [ 19 ] studied the performance of capillary ceiling cooling panels on ceiling surface temperature and indoor thermal environment.…”
Section: Introductionmentioning
confidence: 99%